Exploring the mechanisms of endophytic bacteria for suppressing early blight disease in tomato (Solanum lycopersicum L.) - Sallam, Nashwa M. A.; AbdElfatah, Heba-Alla S.; Khalil Bagy, Hadeel M. M.; Elfarash, Ameer; Abo-Elyousr, Kamal A. M.; Sikora, Edward J.; Sallam, Ahmed (Frontiers in Microbiology, 2023)
Twenty endophytic bacteria isolated from healthy tomato plants were tested in vitro against isolates of Alternaria solani, Alternaria alternata and Curvularia lunata, causal agents of early blight disease of tomato. Of the 20 isolates tested, three (B4, B7, and B17) were considered effective in reducing growth of the pathogens. The three isolates were identified as Enterobacter cloacae HS-6 (B4), Pseudomonas gessardii HS-5 (B 7), and Pseudomonas mediterranea HS-4 (B17) using 16s-rDNA sequencing. Different concentrations of bacterial cultural filtrates at 20, 40, and 60% were tested for their antagonistic effects on the development of the three pathogenic fungi in vitro. The 60% concentration of the bacterial filtrates produced the lowest dry weights of the pathogen isolates. Bacterial culture filtrates were analyzed using Gas Chromatography-Mass Spectrometry (GC-MS),the phenolic compounds exhibited the highest peak area. Under greenhouse conditions, severity of early blight on tomato was significantly less for plants inoculated with culture filtrate of E. cloacae compared to the other bacterial treatments. Realtime PCR was used to examine the expression pattern of the defense response gene β-1.3 glucanase gene in early blight-infected tomato plants, as well as its relationship with E. cloacae. The expression of the gene increased significantly after three days for plants inoculated with C. lunata and E. cloacae, and peaked after five days from inoculation with A. alternata, A. solani and E. cloacae. Based on these results, the endophytic bacterial isolate E. cloacae can be regarded as a good biocontrol agent for preventing early blight of tomato.